Shatkriyakala And Its Applied Aspects - Dr Sharanya R; Dr Rajesh A Udapudi; Dr Sushmitha N G; Dr Rachana A J (Revista Electronica de Veterinaria, 2024)
As per Ayurveda, human body is a symbol of nature. It is composed of 3 basic humors, known as Vata, Pitta and Kapha.(1) When these 3 Doshas are in Prakruta Avastha, it is beneficial for the Shareera as it will be devoid of any Vyadhi. But when these Doshas are in Vikruta Avastha, either as Vruddhi or Kshaya, then it leads to different types of Vyadhi in the Shareera.(2) When Doshas undergo Vruddhi, it manifests a Vyadhi, through various stages, which is very essential for the analysis of a disease, its prognosis, its treatment. These various stages are known as Shatkriyakala, also known as Vyadhikriyakala. In every initial stages, further progression can be stopped to prevent further manifestation of the Vyadhi. This concept also helps the physicians to understand the Samprapti of the Anukta Vyadhi. Chikitsa adopted should be Nidana parivarjana, Pathya sevana initially, later on Sampraptivighatanameva Chikitsa, Doshapratyanika Chikitsa, Vyadhipratyanika Chikitsa and finally Apunarbhava Chikitsa has to be adopted.This review article provides insights the fundamental concept of Ayurveda, which plays a vital role in day to day clinical practice.